Suicídio em Botucatu: um estudo descritivo dos casos ocorridos em 2009 - López, Bárbara Estefania [UNESP] (2015)
Objective: To identify sociodemographic and psychological characteristics associated to cases of suicide recorded in Botucatu during 2009, from a secondary analysis of data obtained through semi-structured interviews with relatives or significant others in order to obtain a psychological autopsy of each case. Methodology: A descriptive study of all cases of suicide recorded in Botucatu County, Brazil, during 2009. Interviews took place between 2 and 11 months after the suicide, coordinated by the County Department of Health Mental Health, and conducted by mental health professional specially trained to this end. Results: Sociodemographic characteristics of the 21 cases of suicide recorded in 2009 as well as factors associated to the 14 cases in which it was possible to perform a psychological autopsy did not differ from data found in the national and international literature. Indication of depression, of mental health treatment and alcohol use were among the abovementioned factors. Most cases had given previous indications of their intention or wish to die in the year before their deaths, with a high demand for health care services in the month previous to the suicide. Conclusion: Suicide prevention strategies that have demonstrated effectiveness elsewhere could also do so in Botucatu